Strategi Guru Pendidikan Agama Islam dalam Membentuk Karakter Kedisiplinan Siswa Kelas X di SMAN 1 Suliki di Era Digital - Anaka, Fingki Trio; Alfurqan, Alfurqan (YASIN, 2025)
This study aims to identify the types of disciplinary violations committed by tenth-grade students, the strategies employed by Islamic Religious Education (Pendidikan Agama Islam or PAI) teachers to instill discipline in the digital era, and the challenges encountered in the process. A qualitative approach was used with a case study method, employing observation, interviews, and documentation techniques. The results show that the most frequent violations include tardiness, dress code infractions, and misconduct during lessons. In addressing these issues, PAI teachers apply strategies such as role modeling, instilling disciplinary values through instruction, and fostering habitual disciplined behavior in students’ daily activities. These strategies are implemented continuously so that disciplinary values become part of the students’ character. The main challenges in applying these strategies include students’ low awareness of the importance of discipline, unsupportive social environments, and the suboptimal role of parents in character development at home. This study affirms the crucial role of teachers in shaping students' discipline, particularly through consistent, contextual, and relevant approaches aligned with the dynamics of digital life today. The practical implications of this study encourage synergy between schools, families, and social environments in instilling discipline as a core component of character education.